2015
DOI: 10.1017/jfm.2015.80
|View full text |Cite
|
Sign up to set email alerts
|

High spatial and temporal resolution study of shock wave reflection over a coupled convex–concave cylindrical surface

Abstract: Studying the nature of transient reflections of shock waves from surfaces is important in many engineering fields, e.g. blast protection, supersonic flights, shock focusing, medical and industrial applications and more. The recent advancements in this field reveal that the major obstacle in better understanding this phenomenon by means of experimental investigations is the limited temporal and spatial resolution. An alternative approach to commonly used high-speed photography is based on the use of a single-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…They showed that an additional Mach stem configuration is formed on the original MR. This was also shown experimentally by Ram, Geva & Sadot (2015). A similar qualitative analysis of RR over segments of wedges forming a convex surface was performed by Wang & Zhai (2020).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…They showed that an additional Mach stem configuration is formed on the original MR. This was also shown experimentally by Ram, Geva & Sadot (2015). A similar qualitative analysis of RR over segments of wedges forming a convex surface was performed by Wang & Zhai (2020).…”
Section: Introductionsupporting
confidence: 85%
“…The following subsections present concise descriptions of the numerical computations, experimental procedure, validation and post-processing. For further information about the computations and extended validation, the interested reader is referred to Geva et al (2013), Ram et al (2015) and Geva, Ram & Sadot (2018).…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, when using the Phantom V711 camera, the thickness of the dark band was roughly equal to one pixel (450 µm). However, when using the Nikon D90, it was about 10 pixels (270 µm), similar to previous results (Ram et al 2015).…”
Section: Visualization Setupsupporting
confidence: 91%
“…Various experimental visualization techniques have been performed in shock tube setups to determine the transition angle using either high temporal imaging or spatial imaging (Geva et al 1990; Kleine et al 2014;Mouton 2006;Naidoo & Skews 2011;Ram et al 2015;Skews & Kleine 2010;Skews & Blitterswijk 2011). Technological advances of high temporal imaging equipment have made these systems readily available to many researchers.…”
Section: Introductionmentioning
confidence: 99%